Effect of rare earth Ce on the microstructure, physical properties and thermal stability of a new lead-free solder - Chen W.; Kong J.; Chen W.J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper, in order to develop a low silver content lead-free solder with good overall properties, a newly designed solder alloys of Sn-0.3Ag-0.7Cu-20Bi-xCe type, with addition of varying amounts of rare earth Ce (0.05 mass%, 0.1 mass% and 0.2 mass%) were studied. The melting temperature of Sn-0.3Ag- 0.7Cu can be decreased substantially through addition of 20 mass% Bi; while the segregation of Bi element in the microstructure of the as-cast alloys can be relieved by micro-alloying with trace amount of rare earth Ce. Besides, aging treatments (160°C held for 6 h) of these solder alloys imply that appropriate amount of Ce addition can not only depress the diffusion induced aggregation of Bi in the microstructure but promote the homogenization during annealing. Compared with Bi-free Sn-0.3Ag-0.7Cu solder, Sn-0.3Ag-0.7Cu- 20Bi exhibits better wettability. More excitingly, the wetting property of Sn-0.3Ag-0.7Cu-20Bi can be further improved by doping little amounts of Ce, especially 0.5 mass%, in which case the spreading area of the solder can be increased to the largest extent. On the whole, the present study reveals that Sn-0.3Ag-0.7Cu- 20Bi-xCe (x=0.05-0.1) is a promising lead-free solder candidate considering the microstructure, melting temperature and wetting properties.